Mengoptimalkan Pendidikan Islam melalui Pemasaran Digital: Pengaruhnya pada Efektivitas Pembelajaran dan Kualitas Pendidikan di Madrasah Ibidaiyah - Muslim, Bukhori; Kunta, Ittaqillah Haitsuma; Hefniy (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study aims to explore the influence of digital marketing on the effectiveness of learning and the quality of education at MI Miftahul Ulum Banyuanyar Lor, Probolinggo Regency. The location of this study was chosen because this Madrasah has begun to integrate digital technology into the learning process. The research method used is qualitative descriptive with a case study approach, involving interviews with the principal, vice principal for curriculum, five educators, two students, and two parents of students. The data obtained through interviews and observations were then analyzed to see how digital marketing is implemented in this Madrasah. The results of the study show that the use of social media and other digital platforms increases interaction between schools, students, and parents, and makes learning more interesting and interactive. Digital marketing makes it easier for students to access teaching materials more flexibly. However, there are challenges related to limited internet access and the influence of social media on students' learning concentration. In conclusion, digital marketing has great potential to improve the quality of Islamic education in this Madrasah, but proper supervision and regulation are needed so that technology is used effectively and does not interfere with students' focus on learning.